2023
DOI: 10.1210/clinem/dgad186
|View full text |Cite
|
Sign up to set email alerts
|

Central Sensitivity to Free Triiodothyronine With MAFLD and Its Progression to Liver Fibrosis in Euthyroid Adults

Abstract: Background Impaired sensitivity to thyroid hormones has been demonstrated to be positively associated with the prevalence of metabolic disorders. However, the relationship between sensitivity to thyroid hormones and metabolic dysfunction-associated fatty liver disease (MAFLD) and liver fibrosis remained unclear. We aimed to determine the associations of thyroid hormone sensitivity indices with MAFLD and its progression to liver fibrosis in Chinese euthyroid adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The morbidity of MAFLD raised with increasing TFQI FT3 and FT3/FT4 levels when multiple potential confounders were adjusted. From the further analysis, subjects in the highest quartile of TFQI FT3 and FT3/FT4 had the notably highest MAFLD risk compared to the three lower quartile groups, which conformed to the findings of Wan et al 32 The research carried out by Lai et al 25 also expressed that TFQI FT3 and FT3/FT4 were closely associated with abnormal blood lipid as well as hepatic steatosis in populations with euthyroidism. This result further provided feasibility for preventing the progression of MAFLD by altering thyroid sensitivity.…”
Section: Discussionsupporting
confidence: 83%
“…The morbidity of MAFLD raised with increasing TFQI FT3 and FT3/FT4 levels when multiple potential confounders were adjusted. From the further analysis, subjects in the highest quartile of TFQI FT3 and FT3/FT4 had the notably highest MAFLD risk compared to the three lower quartile groups, which conformed to the findings of Wan et al 32 The research carried out by Lai et al 25 also expressed that TFQI FT3 and FT3/FT4 were closely associated with abnormal blood lipid as well as hepatic steatosis in populations with euthyroidism. This result further provided feasibility for preventing the progression of MAFLD by altering thyroid sensitivity.…”
Section: Discussionsupporting
confidence: 83%
“…Another study confirmed that TFQI was the indicator of resistance to thyroid hormones and was associated with diabetes and hypertension in euthyroid Tehranian populations [41]. Recently, emerging studies investigated the relationship between sensitivity to thyroid hormones, metabolic disorders, and non-alcoholic fatty liver disease in Chinese subjects [18][19][20]42]. However, the influencing factors of thyroid hormone sensitivity is unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequently, Teng et al demonstrated that impaired sensitivity to thyroid hormones was related to higher risks of cardiovascular disease and hyperuricemia and a lower risk of obesity in patients with subclinical hypothyroidism [18]. Recently, the association of impaired sensitivity to thyroid hormones with high levels of homocysteine [17], components of metabolic syndrome [19], and non-alcoholic fatty liver disease [20] were also revealed. However, the influencing factors of sensitivity to thyroid hormones and whether vitamin D deficiency is correlated with reduced sensitivity to thyroid hormones are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Education level was classified into high school education or lower, or education beyond high school ( 31 ). Smoking was classified as current smokers (those who have smoked ≥100 cigarettes and smoke currently), ex-smokers (who have smoked ≥100 cigarettes but do not smoke currently), and nonsmokers ( 24 ). Alcohol consumption was reported as standard drinks and converted to grams by multiplying by 14.…”
Section: Methodsmentioning
confidence: 99%
“…Central resistance phenomena affect the feedback loop set point within the central nervous system, while peripheral resistance phenomena diminish the metabolic effects of hormones ( 20 ). Impaired thyroid sensitivity was associated with metabolic disorders, including osteoporosis ( 22 ), carotid plaque ( 23 ), and metabolic dysfunction-associated fatty liver disease ( 24 ). A study has indicated that elevated levels of resistance to thyroid hormone indices are associated with diabetes-related mortality in the general population of the United States ( 20 ).…”
Section: Introductionmentioning
confidence: 99%